Assessment of microorganism presence on instruments used in the periodontics area of a university pre-professional practice clinic - Avilez-Abad, María Alejandra (2025)
Objective: To assess the presence of microorganisms on the surfaces of sterile instruments in the periodontics area of a university pre-professional practice clinic. Materials and methods: A descriptive and observational study, in which 100 randomly selected samples of periodontics instruments were selected. The samples collected were analyzed using cultures on specific media, including blood agar, Sabouraud agar, and eosin methylene blue agar, which enabled the primary identification of four classes of microorganisms: Gram-positive cocci, Gram-positive bacilli, Gram-negative bacilli, and yeasts. Results: Of the instruments analyzed, 19% (n = 19) were contaminated. The highest contamination rate was observed in Gracey 3/4 periodontal curettes, with 30% (n = 12), in which only gram-positive cocci were identified, with no positive results for gram-positive bacilli, gram-negative bacilli, or yeasts. Conclusions: Sterilization was not completely effective in all instruments, as some showed contamination with Gram-positive cocci.